Interdependence between WTI Crude Oil Prices and the US Equity Market - Pruchnicka-Grabias, Izabela (International Journal of Energy Economics and Policy, 2022)
The author checks the cointegration between WTI oil market and the US market of stocks represented by the S&P index. As it turns out not to exist, short-term relations are investigated. The study confirms that crude oil market significantly influences the stock market in the short run, however it does not give an unambigous answer if this impact is made by oil itself or together with the GBP/USD currency rate. Furthermore, the relation does not go in another direction which means that the stock market has no impact on the oil market. The Unrestricted Vector Autoregression model is built. The author uses weekly data and the research period is from April 1990 to May 2021. The study implies that stable crude oil prices are desirable in order not to destabilize stock markets whose instability threatens the real economy. Conclusions are vital for a wide group of entities such as policy makers, authorities, institutional and individual investors, as well as other financial market participants.